Chocolat - Brown, David, 1916-2010; Golden, Kit; Holleran, Leslie; Jacobs, Robert Nelson; Hallstrm̲, Lasse; Binoche, Juliette, 1964-; Dench, Judi, 1934-; Molina, Alfred, 1953-; Olin, Lena; Depp, Johnny; Harris, Joanne, 1964- (Miramax collector's series, 2001)
When a single mother and her young daughter move to rural France and open a chocolate shop - with Sunday hours - across the street from the local church, they are met with some resistance from the rigidly moral community. But as soon as the townspeople discover their delicious products, their attitudes begin to change.